2020
DOI: 10.2183/pjab.96.031
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous production of fungal natural products: Reconstitution of biosynthetic gene clusters in model host <i>Aspergillus oryzae</i>

Abstract: While exploring phytotoxic metabolites from phytopathogenic fungi in the 1970s, we became interested in biosynthetic enzymes that catalyze Diels–Alder reactions involving biosynthesis of several phytotoxins that we isolated. Target enzymes were successfully characterized, and this triggered the identification of various Diels–Alderases in a recent decade. Through our Diels–Alderase project in 1990s, we recognized a highly efficient expression system of various biosynthetic genes with Aspergillus or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…With the advance of synthetic biology tools and methods, microbes including Escherichia coli , S. cerevisiae , Aspergillus nidulans , and A. oryzae have been developed as efficient heterologous hosts for the generation of valuable natural products from plants and mushrooms 43 , 44 , 45 . For example, artemisinic acid, a precursor of artemisinin, is produced in an engineered S. cerevisiae by expression a plant dehydrogenase and a second cytochrome, with the titer of 25 g/L 46 .…”
Section: Discussionmentioning
confidence: 99%
“…With the advance of synthetic biology tools and methods, microbes including Escherichia coli , S. cerevisiae , Aspergillus nidulans , and A. oryzae have been developed as efficient heterologous hosts for the generation of valuable natural products from plants and mushrooms 43 , 44 , 45 . For example, artemisinic acid, a precursor of artemisinin, is produced in an engineered S. cerevisiae by expression a plant dehydrogenase and a second cytochrome, with the titer of 25 g/L 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that A. oryzae can also be used as a host for heterologous expression of biosynthetic gene clusters for useful secondary metabolites, such as diterpene aphidicolin, which is a specific inhibitor of DNA polymerase α, and plant polyketide curcumin ( Fujii et al, 2011 ; Kan et al, 2019 ). In particularly, a host strain with quadruple selectable markers ( Jin et al, 2004b ) has also been efficiently used for heterologous production of some fungal natural products (e.g., phytotoxic metabolites, basidiomycete terpenes, and plant hormones) by reconstituting these biosynthetic gene clusters in A. oryzae ( Nagamine et al, 2019 ; Takino et al, 2019 ; Oikawa, 2020a , b ). Moreover, the overexpression of laeA gene was also found to promote the overexpression of two clusters of heterologous biosynthetic genes from A. nidulans , resulting in the production of the corresponding metabolite, monacolin K or terrequinone A ( Sakai et al, 2012 ).…”
Section: Production Of Secondary Metabolites In a Oryzae mentioning
confidence: 99%
“…In addition to protein secretion ability, A. oryzae also has a strong synthesis ability, rapid growth, and easy culture, among its advantages. Compared to Escherichia coli and yeast Saccharomyces cerevisiae , A. oryzae has a strong posttranslational modification function; therefore, it is widely used to produce a variety of enzyme preparations ( Lissau et al, 1998 ; Hama et al, 2008 ; Merz et al, 2015 ) and in recent years has also been used in the production of secondary metabolites ( Yamada et al, 2014 ; Kan et al, 2019 ; Liu et al, 2019 ; Nagamine et al, 2019 ; Morishita et al, 2020 ; Oikawa, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the genus, Aspergillus nidulans has received widespread recognition as a model eukaryote in fungal fundamental research because its morphology, physiology, and growth conditions have been well characterized; in the meanwhile, it is a potential resource and is frequently employed in the production of industrial enzymes [ 13 , 14 ]. These Aspergillus strains have the advantages of easy culture, fast growth, and strong synthetic capacity; therefore, they are also well used in the production of other valuable natural products [ 15 , 16 , 17 , 18 , 19 , 20 ]. In A. nidulans , for example, more than 30 biosynthetic gene clusters have been identified to be associated with specific natural products, although half of them remain uncharacterized [ 21 ].…”
Section: Introductionmentioning
confidence: 99%